The Impact of Life Domains on Juvenile Offending in Bosnia and Herzegovina: Direct, Indirect, and Moderating Effects in Agnew's Integrated General Theory. (November 2014) - Muftić, Lisa R.; Grubb, Jonathan A.; Bouffard, Leana Allen; Maljević, Almir
Objectives: Agnew has proposed an integrative theoretical construct composed of the most influential predictors of crime concentrated within multiple life domains, including the self, family, school, peer, and work. Limited research has explored the impact of life domains on offending. This study presents a partial test of the theory using an international sample. Methods: Nationally representative self-reported data are derived from 1, 756 juveniles residing in Bosnia and Herzegovina who participated in wave 2 of the International Self Report Delinquency Study. A series of multivariate models were run to examine the impact life domains have on crime directly and indirectly, as well as looking at interaction effects among the life domains. Results: Data showcased varying levels of support for the life domains. Across bivariate and multivariate models, the most significant positive relationships between offending and the life domains were evident in the self and peer domains, with the school and family domains exhibiting a negative impact on offending. Furthermore, significant interactive and indirect effects were discovered, primarily for the self and peer domains. Conclusions: This research discovered a moderate level of support for life domains contained within Agnew's integrated theory for offending within an international context.